Proliferation and Osteogenic Differentiation of Mesenchymal Stem Cells Induced by a Short Isoform of NELL-1. (17th February 2015) - Pang, Shen; Shen, Jia; Liu, Yi; Chen, Feng; Zheng, Zhong; James, Aaron W.; Hsu, Ching-Yun; Zhang, Hong; Lee, Kevin S.; Wang, Chunling; Li, Chenshuang; Chen, Xuepeng; et al.
Abstract: Neural epidermal growth factor-like (NEL)-like protein 1 (NELL-1) has been identified as an osteoinductive differentiation factor that promotes mesenchymal stem cell (MSC) osteogenic differentiation. In addition to full-length NELL-1, there are several NELL-1 -related transcripts reported. We used rapid amplification of cDNA ends to recover potential cDNA of NELL-1 isoforms. A NELL-1 isoform with the N-terminal 240 amino acid (aa) residues truncated was identified. While full-length NELL-1 that contains 810 aa residues (NELL-1810 ) plays an important role in embryologic skeletal development, the N-terminal-truncated NELL-1 isoform (NELL-1570 ) was expressed postnatally. Similar to NELL-1810, NELL-1570 induced MSC osteogenic differentiation. In addition, NELL-1570 significantly stimulated MSC proliferation in multiple MSC-like populations such as murine C3H10T1/2 MSC cell line, mouse primary MSCs, and perivascular stem cells, which is a type of stem cells proposed as the perivascular origin of MSCs. In contrast, NELL-1810 demonstrated only limited stimulation of MSC proliferation. Similar to NELL-1810, NELL-1570 was found to be secreted from host cells. Both NELL-1570 expression lentiviral vector and column-purified recombinant protein NELL-1570 demonstrated almost identical effects in MSC proliferation and osteogenic differentiation, suggesting that NELL-1570 may function as a pro-osteogenic growth factor. In vivo, NELL-1570 induced significant calvarial defect regeneration accompanied by increased cell proliferation. Thus, NELL-1570 has the potential to be used for cell-based or hormone-based therapy of bone regeneration. Stem Cells   2015;33:904–915